Sodium permeable and "hypersensitive" TREK‐1 channels cause ventricular tachycardia. Issue 4 (27th February 2017) - Decher, Niels; Ortiz‐Bonnin, Beatriz; Friedrich, Corinna; Schewe, Marcus; Kiper, Aytug K; Rinné, Susanne; Seemann, Gunnar; Peyronnet, Rémi; Zumhagen, Sven; Bustos, Daniel; Kockskämper, Jens; Kohl, Peter; et al.
Abstract: In a patient with right ventricular outflow tract (RVOT) tachycardia, we identified a heterozygous point mutation in the selectivity filter of the stretch‐activated K2P potassium channel TREK‐1 ( KCNK2 or K2P 2.1). This mutation introduces abnormal sodium permeability to TREK‐1. In addition, mutant channels exhibit a hypersensitivity to stretch‐activation, suggesting that the selectivity filter is directly involved in stretch‐induced activation and desensitization. Increased sodium permeability and stretch‐sensitivity of mutant TREK‐1 channels may trigger arrhythmias in areas of the heart with high physical strain such as the RVOT. We present a pharmacological strategy to rescue the selectivity defect of the TREK‐1 pore. Our findings provide important insights for future studies of K2P channel stretch‐activation and the role of TREK‐1 in mechano‐electrical feedback in the heart. Synopsis: A point mutation in the selectivity filter of the stretch‐activated K2P potassium channel TREK‐1 was identified in a patient with right ventricular outflow tract tachycardia. The mutation most likely causes arrhythmias through abnormal sodium permeability and hypersensitivity to stretch‐activation. Analysis of a patient with right ventricular outflow tract tachycardia (RVOT‐VT) led to the identification of a heterozygous mutation, resulting in an Ile to Thr exchange directly preceding the selectivity filter of the K2P potassium channel TREK‐1. The mutation introduces an abnormal sodium permeability and a hypersensitivity to stretch‐activation to TREK‐1 channels. The study suggests that the selectivity filter is directly involved in stretch‐induced activation and desensitization of stretch‐sensitive K2P potassium channels. Increased sodium permeability and stretch‐sensitivity of mutant TREK‐1 channels may trigger arrhythmias in areas of the heart with high physical strain. The findings provide important insights for future studies of K2P channel stretch‐activation and the role of TREK‐1 in mechano‐electrical feedback in the heart. Abstract : A point mutation in the selectivity filter of the stretch‐activated K2P potassium channel TREK‐1 was identified in a patient with right ventricular outflow tract tachycardia. The mutation most likely causes arrhythmias through abnormal sodium permeability and hypersensitivity to stretch‐activation.